Investigation on electrical performance of Sr, Mg, co-doped Na0.5Bi0.5TiO3 oxide ion conductor - WANG Wei-guo (Journal of Materials Engineering, 2019)
Na0.5Bi0.48Sr0.02Ti0.98Mg0.02O2.97 compound was synthesized by solid-state reaction. AC impedance and internal friction spectroscopy were employed to study the electrical performance and oxgyen ion diffusion in the Sr,Mg-co-doped Na0.5Bi0.5TiO3 compounds. The grain conductivity of Na0.5Bi0.48Sr0.02Ti0.98Mg0.02O2.97 sample can reach 5.31×10-4 S/cm at 593 K, an order of magnitude higher than that of the Na0.5Bi0.5TiO3 compound at the same temperature and exceeding the grain conductivity of Na0.5Bi0.5Ti0.98Mg0.02O2.98 sample at 673K. An internal friction relaxation peak was observed. The relaxation parameters can be calculated, E=0.85eV and τ0=7.4×10-14s. Judging from the relaxation parameters and structural analysis, the Sr2+ dopant can amplify the specific free volume. Compared with the Na0.5Bi0.5Ti0.98Mg0.02O2.98 sample, the substantial increase of the grain conductivity for Na0.5Bi0.48Sr0.02Ti0.98Mg0.02O2.97 sample may be derived from the larger specific free volume, higher mobile oxygen vacancy content and better oxygen vacancy mobility.